2011
DOI: 10.1215/00031283-1277510
|View full text |Cite
|
Sign up to set email alerts
|

Intersecting Variables and Perceived Sexual Orientation in Men

Abstract: Sociolinguistic styles tie linguistic resources together into clusters and link them to social contexts of times, groups, places, and activities. Perceptions of masculinity and sexual orientation represent a well-studied area on sociolinguistic perception, offering many variables with potentially relevant social meanings. This study examines social perceptions of guises created by intersecting three masculinity-relevant variables: pitch, /s/-fronting or backing, and (ING). First, 110 online respondents provide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
89
1
13

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 108 publications
(106 citation statements)
references
References 17 publications
3
89
1
13
Order By: Relevance
“…Given that working-class and middle-class adolescent girls are more similar to one another physiologically than to adult men, one must turn to articulatory practices to explain these findings. On the other side of the Atlantic, several studies have identified /s/ as one of the most consistent and most salient cues for the perception of sexual orientation among North American English-speaking men (Campbell-Kibler 2011;Levon 2007;Munson 2007;Munson et al 2006;Zimman 2013; inter alia), which demonstrates that adult men are capable of producing /s/ with a range of frequency profiles. This usually comes in the form of a more negative skew, i.e.…”
Section: Review Of the Literaturementioning
confidence: 98%
See 1 more Smart Citation
“…Given that working-class and middle-class adolescent girls are more similar to one another physiologically than to adult men, one must turn to articulatory practices to explain these findings. On the other side of the Atlantic, several studies have identified /s/ as one of the most consistent and most salient cues for the perception of sexual orientation among North American English-speaking men (Campbell-Kibler 2011;Levon 2007;Munson 2007;Munson et al 2006;Zimman 2013; inter alia), which demonstrates that adult men are capable of producing /s/ with a range of frequency profiles. This usually comes in the form of a more negative skew, i.e.…”
Section: Review Of the Literaturementioning
confidence: 98%
“…It is also clear that this difference is articulatory in nature, and cannot reflect a biophysically predetermined frequency range for sibilants. Far from being limited to Castilian Spanish, a low frequency or retracted /s/ has also been documented in certain varieties of English, often with some kind of link to masculinity and/or workingclassness (Campbell-Kibler 2011;Stuart-Smith 2007). Given that COG for many of the Spanish tokens in Figure 4 are in the range of 4,000-6,000 Hz, this kind of /s/ may not even be perceived as retracted, particularly when paired with a low-pitched voice (Strand 1999).…”
Section: Intra-speaker Analysismentioning
confidence: 99%
“…While listeners may rely on individual phonemes to identify a speaker’s indexical characteristics (Linville, 1998; Mack & Munson, 2012; Munson et al, 2006), it has also been argued (Campbell-Kibler, 2007, 2011; Thomas, 2002; Thomas et al, 2010) that listeners tend to rely on several acoustic cues, such as segmental quality and prosody, and not a single cue, when determining a speaker’s indexical characteristics. With respect to sexual orientation, Campbell-Kibler (2007, 2011) asserted that features such as pitch, differences in production of /s/ and /z/, and the English variable (ING) helped listeners distinguish between gay and heterosexual male talkers of American English.…”
Section: Introductionmentioning
confidence: 99%
“…With respect to sexual orientation, Campbell-Kibler (2007, 2011) asserted that features such as pitch, differences in production of /s/ and /z/, and the English variable (ING) helped listeners distinguish between gay and heterosexual male talkers of American English. The – ing variant enhances the perceived strength of a gay-sounding accent (Campbell-Kibler, 2007), and utterances that contain fronted /s/ and /z/ tokens, compared with mid and backed tokens, increase the perception of gayness (Campbell-Kibler, 2011). Finally, a complex picture emerges when listeners describe speech containing fronted and backed tokens of /s/ along with – ing .…”
Section: Introductionmentioning
confidence: 99%
“…This sensitivity is observable in listener perceptions of a variety of social identities, including social class (Labov 1966and Walker 2007, ethnicity (Purnell, Idsardi & Baugh 1999), gender (Strand 1999), country or region of origin (Campbell-Kibler 2007) and sexual orientation (Campbell-Kibler 2011, Gaudio 1994, Levon 2006, Munson 2011, Munson, McDonald, DeBoe & White 2006, Podesva 2011, Podesva, Roberts & CampbellKibler 2001. Perception studies take advantage of listener sensitivity to social variation and focus on what specific cues trigger evaluations of social identities.…”
Section: Introductionmentioning
confidence: 99%